2007
DOI: 10.1097/01.brs.0000251014.81875.6d
|View full text |Cite
|
Sign up to set email alerts
|

Surgical or Nonoperative Treatment for Lumbar Spinal Stenosis?

Abstract: Although patients improved over the 2-year follow-up regardless of initial treatment, those undergoing decompressive surgery reported greater improvement regarding leg pain, back pain, and overall disability. The relative benefit of initial surgical treatment diminished over time, but outcomes of surgery remained favorable at 2 years. Longer follow-up is needed to determine if these differences persist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
410
2
10

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 481 publications
(435 citation statements)
references
References 20 publications
13
410
2
10
Order By: Relevance
“…By used covariates, the effect of initial pain, disability and accumulation of fulfilment of self-acting exercises on outcome could be controlled. This study is in line with the earlier literature [23], strengthening the concept that ''treatment as usual'' is sufficient postoperatively in LSS. With increasing life expectancy, the incidence and prevalence of LSS will increase in aging population, meaning increase also in rates of LSS surgery.…”
Section: Limitationssupporting
confidence: 91%
See 2 more Smart Citations
“…By used covariates, the effect of initial pain, disability and accumulation of fulfilment of self-acting exercises on outcome could be controlled. This study is in line with the earlier literature [23], strengthening the concept that ''treatment as usual'' is sufficient postoperatively in LSS. With increasing life expectancy, the incidence and prevalence of LSS will increase in aging population, meaning increase also in rates of LSS surgery.…”
Section: Limitationssupporting
confidence: 91%
“…In addition, the benefits of physiotherapy in conservative treatment of LSS have been reported [23,42,43]. There was little evidence available concerning the effect of abdominal muscle training in a clinical setting when planning this study [14].…”
Section: The Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although reduced walking distance is an important component of the symptom complex of lumbar stenosis, the assessment of walking distance is relatively insensitive to change. Studies comparing surgery with conservative treatment for lumbar stenosis also found no differences between treatment groups regarding walking distance, although other outcome measures differed significantly between treatment groups [56,57].…”
Section: Discussionmentioning
confidence: 99%
“…Most implants are used for degenerative spinal diseases, one of which is LSS. The reported successful clinical outcome after bony decompression, the gold standard treatment, is only 64 % and many patients remain to have associated low back pain [5,[7][8][9]. In an effort to improve clinical outcome, a French group introduced a new non-rigid fixation [interspinous process devices (IPDs)] for patients with LSS and associated back pain in 1984: the Wallis system [10][11][12].…”
Section: Interspinous Process Devices Versus Microdecompressionmentioning
confidence: 99%